The situation of women in the labor market in Poland in the light of existing labor law provisions concerning the working time - Ludera-Ruszel, Agata (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
Increasing the share of women on the labour market is an urgent issue that Europe must face in the context of aging society, which is perceived as a threat for the future socio-economic situation of European countries. However, in 2012 women’s participation in the labour market of the European Union was even by 12.2% lower than that of men. Poland was among the few countries with the greatest difference in the share of sexes on the labour market. One reason for women’s lower professional activity is the difficulties in combining work with family responsibilities. For many women maternity means long-term unemployment, or even resignation from a professional career, in relation to difficulties with returning to the labour market. Labour law may have a positive or negative impact on the situation of women on the labour market. An important regulation in this regard is one that regulates working time. Based on the analysis of the applicable regulations from the Labour Code, the article focuses on the available ways of working time management by the employee in the context of possible combining of work and the fulfilment of family responsibilities.

Zwiększenie udziału kobiet na rynku pracy pozostaje pilną kwestią, z jaką zmierzyć się musi Europa w kontekście zjawiska starzenia się społeczeństwa, które jest postrzegane w kategoriach zagrożenia dla sytuacji społeczno-gospodarczej państw europejskich. Tymczasem w 2012 r. stopień partycypacji kobiet na rynku pracy był aż o 12,2% mniejszy od mężczyzn. Polska znalazła się w grupie państw o największej różnicy w udziale między kobietami a mężczyznami na rynku pracy. Jedną z przyczyn niższej aktywności zawodowej kobiet są trudności w łączeniu pracy zawodowej z obowiązkami rodzinnymi. Dla kobiet macierzyństwo oznacza długotrwałe bezrobocie, a nawet rezygnację z pracy zawodowej, w przypadku trudności z powrotem na rynek pracy. Prawo pracy może wpływać pozytywnie bądź negatywnie na sytuację kobiet na rynku pracy. W tym zakresie istotne znaczenie mają przepisy dotyczące czasu pracy. W oparciu o analizę obowiązujących regulacji Kodeksu pracy z zakresu czasu pracy podjęte rozważania koncentrują się na dostępnych sposobach zarządzania czasem pracy przez pracownika w kontekście możliwości łączenia pracy zawodowej z realizacją obowiązków rodzinnych.
Sytuacja kobiet w rynku pracy w Polsce w świetle obowiązujących regulacji prawa pracy dotyczących czasu pracy
Keywords: labour law; working time; work-life balance; prawo pracy; czas pracy; równowaga pomiędzy życiem zawodowym a osobistym